Now let me see where I was: Understanding how Lifelogs mediate memory. - Kalnikaite, Vaiva; Sellen, Abigail; Whittaker, Steve; Kirk, David (Proceedings of CHI 2010, 2010)
Lifelogging technologies can capture both mundane and important experiences in our daily lives, resulting in a rich record of the places we visit and the things we see. This study moves beyond technology demonstrations, in aiming to better understand how and why different types of Lifelogs aid memory. Previous work has demonstrated that Lifelogs can aid recall, but that they do many other things too. They can help us look back at the past in new ways, or to reconstruct what we did in our lives, even if we don’t recall exact details. Here we extend the notion of Lifelogging to include locational information. We augment streams of Lifelog images with geographic data to examine how different types of data (visual or locational) might affect memory. Our results show that visual cues promote detailed memories (akin to recollection). In contrast locational information supports inferential processes – allowing participants to reconstruct habits in their behaviour.